Mediation of attitude toward brand on the relationship between service brand credibility and purchase intentions - Muhammad Sheeraz; Aamir Khan Khattak; Shahid Mahmood; Nadeem Iqbal (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2016)
The current study empirically examine the interrelationship between service brand credibility, attitude toward brand and purchase intentions. Furthermore, the study also investigates the mediating role of attitude toward brand in understanding the relationship between brand credibility and purchase intentions in service sector of Pakistan. The results are based on the perceptions of universities students (n = 309) regarding fast food restaurants and transport services in Pakistan. Linear regression and Sobel test are used to examine the proposed hypotheses. The results reveal that both brand credibility and attitude toward brand positively impact purchase intentions. The attitude toward brand partially mediates the relationship between brand credibility and purchase intentions. This study provides insights for advertisers and brand managers to manage brand communication campaigns more consciously and deliberately in service sector. The limitations are also discussed along with recommendations for future research.
Keywords: 330; brand credibility; attitude toward brand; purchase intentions; mediation; service brands in Pakistan